Estimates of the Southern Ocean general circulation improved by animal‐borne instruments. Issue 23 (3rd December 2013) - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean‐Benoit; Bailleul, Frederic; Costa, Daniel P.; Huckstadt, Luis A.; Goetz, Kimberly T.; Kovacs, Kit M.; et al.
Abstract [1] Over the last decade, several hundred seals have been equipped with conductivity‐temperature‐depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal‐derived hydrographic data is now available, consisting of more than 165, 000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal‐derived data substantially modifies the estimated surface mixed‐layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.